2007
DOI: 10.1074/jbc.m610943200
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Is an Essential Mediator of Osteogenesis That Links the p204 Protein to the Cbfa1 Transcription Factor Thereby Increasing Its Activity

Abstract: Bone formation requires the coordinated activity of numerous proteins including the transcription factor core-binding factor ␣1 (Cbfa1). Deregulation of Cbfa1 results in metabolic bone diseases including osteoporosis and osteopetrosis. The retinoblastoma protein (pRb) that is required for osteogenesis binds Cbfa1. We reported earlier that the p200 family protein p204, which is known to be involved in the differentiation of skeletal muscle myotubes, cardiac myocytes, and macrophages, also serves as a cofactor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 62 publications
3
53
0
Order By: Relevance
“…pRb was found to interact with Cbfa1, and it was required for Cbfa1-mediated osteogenesis (Thomas et al, 2001). pRb is also needed for the association of p204 and Cbfa1 and enhancements of osteogenesis by p204 (Luan et al, 2007). Id2 does not disturb the association of p204 and Cbfa1 ( Figure 7B), and same is also true for the association of pRb and Cbfa1 (data not shown), suggesting that p204 and/or pRb bind to Cbfa1 with higher affinity than does Id2.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…pRb was found to interact with Cbfa1, and it was required for Cbfa1-mediated osteogenesis (Thomas et al, 2001). pRb is also needed for the association of p204 and Cbfa1 and enhancements of osteogenesis by p204 (Luan et al, 2007). Id2 does not disturb the association of p204 and Cbfa1 ( Figure 7B), and same is also true for the association of pRb and Cbfa1 (data not shown), suggesting that p204 and/or pRb bind to Cbfa1 with higher affinity than does Id2.…”
Section: Discussionmentioning
confidence: 72%
“…We previously reported that p204 acted as a transcriptional coactivator of Cbfa1 and therefore enhanced osteoblast differentiation (Liu et al, 2005) and that pRb is an essential linker between p204 and Cbfa1, thereby increasing its activity (Luan et al, 2007) during the differentiation of pluripotent C2C12 to osteoblast induced by BMP-2. In this study, we report that Id proteins directly associate with Cbfa1 and inhibit Cbfa1-mediated osteogenic differentiation and that p204 overcomes these inhibitions by Id proteins, and we focus on the molecular mechanisms underlying these processes.…”
Section: © 2008 By the American Society For Cell Biology 2113mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that p204 associates with Cbfa1 and plays an important role in osteoblast differentiation. 12,24,25 Given that Cbfa1 is also required for the hypertrophic chondrocyte differentiation, we sought to determine whether p204 was also involved in the chondrocyte differentiation. We first examined the expression of p204 in growth plate chondrocytes using immunohistochemistry on tibial growth plates of mouse embryos on postcoital day 18.5.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, forced expression of p204 strongly repressed the IL-3-and M-CSF-dependent proliferation, whereas it promoted the M-CSF-induced macrophage differentiation of FD-Fms cells. 23 We previously reported that p204 acted as a transcriptional coactivator of Cbfa1 and therefore enhanced osteoblast differentiation 12 and that pRb is an essential linker between p204 and Cbfa1 thereby increasing its activity; 24 p204, pRb, Cbfa1 and Ids form a protein interaction network and act in concert in regulating the differentiation of pluripotent C2C12 to osteoblasts. 25 In this study, we describe the expression and function of p204 in hypertrophic chondrocyte differentiation as well as the molecular mechanism involved.…”
mentioning
confidence: 99%